Korelasi Tuhan dan Demokrasi di Indonesia Setelah Pemerintahan Orde Baru (Lex Jurnalica, 2013)
AbstractConcerning performing change democratizes before and after orde baru governance, therefore arises changing The Infinite and democracy correlation at Indonesian. At in this case The Infinite don't act as the infinite but It more tend most manifest as footing in acting. Domicile The Infinite in democratizes to lie under people power. God who are in democratize wherewith as a substance for all WNI, it can be parallelized by God in agnostic's scope and atheism. As suggest as that mandatory government works to equal college party to give studies visceral for society to extend about The Infinite and democracy. It also take in positive order in order not to happens adverse action that democratizes for god's sake. One of example it maltreatment an ethnical, dislike step-up to minority religion, reject to liyan's clan or voice take process that undemocratic. Keywords: god, democracy, pancasilaÂ AbstrakTerkait perubahan pelaksanaan demokrasi sebelum dan setelah pemerintahan orde baru, maka memunculkan perubahan korelasi Tuhan dan demokrasi di Indonesia. Di dalam hal ini Tuhan tidak bertindak sebagai tuhan namun Ia lebih cenderung terejawantah sebagai pijakan dalam bertindak. Kedudukan Tuhan di dalam demokrasi berada di bawah kekuasaan rakyat. Tuhan yang berada di dalam demokrasi bermakna sebagai suatu zat bagi seluruh WNI, hal ini dapat disejajarkan dengan tuhan dalam lingkup agnostik dan atheis. Sebagai saran agar pemerintah wajib bekerja sama dengan pihak perguruan tinggi untuk memberi telaah mendalam bagi masyarakat luas tentang Tuhan dan demokrasi. Hal ini juga membawa pesan positif agar tidak terjadi tindakan merugikan yang mengatasnamakan demokrasi demi Tuhan. Salah satu contohnya penganiayaan suatu etnis, peningkatan kebencian kepada agama minoritas, penolakan kepada kaum liyan atau proses pengambilan suara yang tidak demokratis.Kata kunci: tuhan, demokrasi, pancasila